(3QGjT h GdJMdjd GdfaSj (B/s - (3bjS, NRYd LhGO s ((3dHfGf (B-(3HjQhJ (B:s (3OGQ GdMOGKI ,s, 1983)
(3QGjT h GdJMdjd GdfaSj(B-(3GdSjQI GdOGJjI dhdjge QGjT(B-(3GdhUSI GdGNjQI(B:(3Nha Ydi GdefLRGJs
Keywords: (3QGjT h GdJMdjd GdfaSjs; (3Yde GdfaSs